ENHANCING CREATIVE THINKING IN FINE ARTS THROUGH THE USE OF AR AND VR TECHNOLOGIES - Muratova Dilnavoz Jamshid qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
The rapid advancement of digital technologies has significantly influenced contemporary art education. Augmented Reality (AR) and Virtual Reality (VR) technologies provide innovative opportunities to enhance creative thinking in fine arts by immersing students in interactive and visually rich learning environments. These technologies allow learners to explore artistic concepts, experiment with forms and colors, and interact with virtual art spaces beyond the limitations of traditional classrooms. This article examines the pedagogical potential of AR and VR technologies in developing students’ creative thinking in fine arts education. The study highlights methodological approaches, learning benefits, and the impact of immersive technologies on students’ imagination, originality, and creative expression. The findings suggest that the integration of AR and VR technologies fosters higher levels of creativity, engagement, and artistic competence among learners.